Manajemen Risiko Keselamatan dan Kesehatan Kerja pada Perawat Menggunakan Hazard Identification Risk Assessment And Risk Control - Subagja Dwi Permana; Tatiana Siregar (Fakultas Kesehatan Masyarakat Universitas Andalas, 2023)
A nurse in providing nursing care cannot be separated from risks that can cause work accidents. Occupational accident is an unexpected event that is not expected when doing work. Based on work-related accident and disease recapitulation data at X Depok Hospital, it shows that during the 2018-2022 period there were 6 incidents of needle sticks and 2 incidents of nurses slipping. The purpose of this study is to determine OSH risk management using Hazard Identification Risk Assessment and Risk Control. This research is a qualitative research. Data collection methods used are observation and interviews. The informants in this study were divided into main informants, namely the 3 heads of rooms and supporting informants, namely the team leader. Based on the research results, it is known that there are 7 work activities that are identified as having potential hazards. The hazards identified were biological hazard, namely the possibility of contracting the patient's disease, ergonomic hazard, namely waist injury, low back pain, HNP and physical hazard, namely injured hands. The risk assessment identified 1 extreme risk work activity, 4 high risk work activities and 2 low risk work activities. Control efforts are carried out namely the existence of Standard Operating Procedures and Personal Protective Equipment.